Light and freshwater discharge drive the biogeochemistry and microbial ecology in a sub-Arctic fjord over the Polar night - Vonnahme, T. R.; Klausen, L.; Bank, R. M.; Michellod, D.; Lavik, G.; Dietrich, U.; Gradinger, R. (Frontiers in Marine Science, 2022)
The polar night has recently received increased attention as a surprisingly active biological season. Yet, polar night microbial ecology is a vastly understudied field. To identify the physical and biogeochemical parameters driving microbial activity over the dark season, we studied a sub-Arctic fjord system in northern Norway from autumn to early spring with detailed monthly sampling. We focused on the impact of mixing, terrestrial organic matter input and light on microbial ecosystem dynamics. Our study highlights strong differences in the key drivers between spring, autumn, and winter. The spring bloom started in March in a fully mixed water column, opposing the traditional critical depth hypothesis. Incident solar radiation was the key driver maximum Chlorophyll was reached in April. The onset of the autumn phytoplankton bloom was controlled by vertical mixing, causing nutrient upwelling and dilution of zooplankton grazers, which had their highest biomass during this time. According to the dilution-recoupling hypothesis grazer dilution reduced grazing stress and allowed the fall bloom formation. Mixing at that time was initiated by strong winds and reduced stratification as a consequence of freezing temperatures and lower freshwater runoff. During the light-limited polar night, the primary production was extremely low but bacteria continued growing on decaying algae, their exudates and also allochthonous organic matter. A melting event in January could have increased input of organic matter from land, supporting a mid-winter bacterial bloom. In conclusion, polar night biogeochemistry and microbial ecology was not only driven by light availability, but strongly affected by variability in reshwater discharge and allochthonous carbon input. With climate change freshwater discharge will increase in the Arctic, which will likely increase importance of the dynamics described in this study.